HUMAN RESOURCE MANAGEMENT INNOVATION IN INCREASING AGRICULTURAL PRODUCTIVITY - Farida, Farida (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
Agriculture as a strategic sector requires an innovative management approach to face global challenges in meeting increasing food needs. This research aims to investigate and analyze the implementation of human resource management (HR) innovation in the agricultural sector with a focus on increasing agricultural productivity. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of Human Resources (HR) management innovations in the agricultural sector has a positive impact on production results and farmer welfare. Steps such as contextual training, application of information and communication technology, performance-based approaches, as well as empowerment through the formation of groups or cooperatives, and risk management make a significant contribution to increasing agricultural efficiency and sustainability. Farmers involved in these innovations demonstrate improved skills, access to information, efficient collaboration and the ability to manage risk. Thus, the results of this research provide a strong basis for stakeholders to adopt and expand the implementation of HR management innovations to encourage more adaptive, competitive and sustainable agriculture in the future.